Understanding the role of nickel on the hydrogen storage capacity of Ni/MCM-41 materials - Carraro, Paola María (2016)
In this study, we prepared MCM-41 mesoporous materials modified with different Ni contents, as promising materials for hydrogen storage. We focused on the role of dispersed nickel as a way of promoting the interaction with hydrogen as an alternative to improve hydrogen storage materials. In addition, the reducibility of Ni/MCM-41 materials was studied, and the hydrogen adsorption in the reduced materials was evaluated, in order to compare the behaviour of reduced and unreduced Ni/MCM-41 materials in hydrogen storage at 77 and 293 K. Hydrogen adsorption isotherms were measured at 77 K and 293 K, and at low and high-pressure conditions respectively. The results obtained show that the amount of hydrogen stored was highly enhanced by the dispersion of small amounts of Ni nanoparticles both at 77 and 293 K. Experimental techniques such as TPR, XPS, N2 adsorption-desorption and computational methods (DFT) were used in order to interpret the results and contribute to the understanding of hydrogen adsorption on Ni/MCM-41 materials.